USAHA MEMAKNAI SAKRAMEN PENGUATAN UNTUK MENINGKATKAN KETERLIBATAN HIDUP MENGGEREJA DAN MEMASYARAKAT OMK WILAYAH PAROKI KRISTUS RAJA CIGUGUR - Setiawati, Anastasia Mela; Wulung, F.X Heryatno Wono (CREDENDUM: Jurnal Pendidikan Agama, 2024)
This writing is motivated by the lack of understanding of the Sacrament of Confirmation among the Catholic youth of the Christ the King Parish in Cigugur. The purpose of this writing is to investigate the level of understanding of the Catholic youth regarding the Sacrament of Confirmation and to identify the various aspects of life involvement that interest them. The author chooses qualitative research, employing literature review and field research methods. The findings indicate that the Catholic youth's understanding of the Sacrament of Confirmation is good enough, but there is still needs improvement. Some of them express their desire to do the interfaith dialogues. Several of them state their readiness to participate in activities organized by other organizations. Overall, it is evident that the Catholic youth have not yet realized that their life participation is a gift of the Holy Spirit following the reception of the Sacrament of Confirmation. It is true that the process of understanding and meaning-making takes time and is not instantaneous. Then it’s good for young people to receive meeting that helps them reflect on the fruit of the Sacrament of Confirmation and meeting that helps young people interpret every life experience. Keywords: participation in church and community life, Catholic youth, Sacrament of Confirmation, efforts to create meaning.